Traduire l’ironie des rongeurs : fonction et efficacité rhétorique et aspects rhétorico-pragmatiques de la traduction du discours ironique des rats fabuleux de La Fontaine - Valyon, Eszter Etelka (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The present paper discusses the rhetorical/pragmatic dimensions and levels of verbal irony through the example of a famous La Fontaine ’s Rat-fable. Verbal irony performs a pragmatic function, making use of a potential contrast between expected and experienced events. This makes verbal irony generally funnier, more criticizing, more expressive of a difference between expected and ensuing events and more protective of the speaker than literal remarks. This paper also proposes a study of verbal irony, as purely pragmatic phenomenon, in order to provide a plausible analysis of the allegoric ‘ironicalness’. In this case study of La Fontaine ’s Rat retired from the World, I will argue that pragmatic enrichment processes have effects on translation. The translator, as a communicator, may translate not what was linguistically encoded in the original text but rather what was propositionally communicated. This will result in discrepancies in style between source and target texts. Enrichment done on cultural/contextual grounds can modify the source to a greater extent, and its motivation is more subjective, justified only on the translator ’s choice and judgment.